Analisis Hukum Ekonomi Syariah Terhadap Ketidaksesuaian Harga Dalam Transaksi Jual Beli Buah-Buahan - Sunarsa, Sasa; Karim, Dede Abdul (STAI Al Musaddadiyah Garut, 2025)
Buying and selling transactions are a very common economic activity in society, including the sale of fruit. However, in practice, discrepancies between the agreed and paid prices are often found, either due to misinformation, lack of clarity in the contract, or an element of non-transparency on the part of one of the parties. This study aims to analyze price discrepancies in fruit sales transactions from the perspective of Islamic Economic Law. The research method used is a qualitative method with a descriptive-analytical approach. Data were collected through interviews with business actors, buyers, and religious leaders, and supplemented by a literature review of relevant primary and secondary sources. The analysis was conducted using the basic principles of Islamic Economic Law such as justice ('adl), openness (transparency), and mutual agreement (antaradhin). The results of the study indicate that price discrepancies in fruit sales transactions have the potential to cause injustice and lead to practices that are contrary to Islamic principles. In Islamic Economic Law, price clarity is a valid requirement for buying and selling (ba'i), and any form of deception or unclear information can be categorized as gharar (uncertainty), which is prohibited in Islam. Therefore, to create fair and sharia-compliant transactions, transparency, clarity of contracts, and education for business actors about the ethics of buying and selling in Islam are required. Keywords: sharia economic law; buying and selling; price discrepancy; fruits.